387 MITRAL VALVE MORPHO-FUNCTIONAL FEATURES DURING THE ACUTE AND RECOVERY PHASE IN PATIENTS WITH TAKOTSUBO SYNDROME. (15th December 2022) - Vitale, Enrica; Santoro, Francesco; Cetera, Rosa; Ragnatela, Ilaria; Mallardi, Adriana; Leopizzi, Alessandra; Matera, Annalisa; Manuppelli, Vincenzo; Correale, Michele; Iacoviello, Massimo; Brunetti, Natale Daniele
Abstract: Background: Acute mitral valve regurgitation is known to be associated with a severe prognosis in patients affected by Takotsubo syndrome (TTS). The mechanisms involved are different and related to various pathogenesis such as cordal or mitral anterior leaflet (LAM) systolic anterior motion (SAM) and tethering of the mitral valve. Aim of the study: to compare mitral valve morpho-functional features and concomitant left ventricle (LV) abnormalities by transthoracic echocardiography in patients during the acute and recovery phase of Takotsubo syndrome. Methods: 24 consecutive patients were enrolled from a multicenter prospective registry of TTS from July 2007 to February 2022. Through transthoracic echocardiography, LV ejection fraction, LV end-diastolic and end-systolic diameters and volumes, left atrium antero-posterior diameter and end-systolic volume, mitral anulus diameter, prevalence of mitral valve regurgitation, of LV outflow tract obstruction (LVOTO), coaptation depth and tenting area were collected during the acute and recovery phase of takotsubo syndrome. Results: LVEF at admission was 39.6 ± 7.8% vs 60.5 ± 4% at functional recovery (p<0.001). LVEDV, LVESV and LVESVi were found to be higher during the acute phase when compared to the recovery phase (103.8 ± 28.9 vs 89.7 ± 23.4 ml, p=0.012; 59.8 ± 17.2 vs 35.1 ± 10.1 ml, p< 0.001; and 36.1 ± 9 vs 20.6 ± 5.4 ml/m2, p<0.001 respectively). No statistically significant differences were found between admission and recovery phase in term of mitral annular dimension (32.3 ± 4.6 vs 32.5 ± 4.1 mm, p=0.825), tenting area (2.3 ± 0.6 vs 2.2 ± 0.7 cm 2, p=0.445), proximal thickness and length of both of the mitral leaflets, while coaptation depth was higher during the acute phase in comparison to functional recovery (1.1 ± 0.2 vs 1 ± 0.3 cm, p=0.018). 10 patients (41%) presented with moderate/ severe mitral insufficiency and 5 patients of them (20% of the general population) downgraded to mild at recovery. Among the patients with values of LVEDV higher than 104 mL, LVESV higher than 43 mL, LVESVi higher than 25 mL/m 2 and coaptation depth higher than 1.1 cm during the acute phase, 4 out of 5 patients experienced a downgrade of the severity of mitral valve regurgitation. Conclusions: Left ventricle end-diastolic volume and coaptation depth are statistically different during the acute and recovery phase. Among the patients who experienced a downgrading of the severity of mitral valve regurgitation, higher values of LVEDV, LVESV, LVESVi and coaptation depth during the acute phase were found.